CART PEPTIDE IN THE NUCLEUS ACCUMBENS REGULATES PSYCHOSTIMULANTS: CORRELATIONS BETWEEN PSYCHOSTIMULANT AND CART PEPTIDE EFFECTS - JOB, MARTIN O. (Neuroscience, 2017)
In this study, we reexamined the effect of CART peptide on psychostimulant (PS)-induced locomotor activity (LMA) in individual rats. The Methods utilized were as previously published. The PS-induced LMA was defined as the distance traveled after PS administration (intraperitoneal), and the CART peptide effect was defined as the change in the PS-induced activity after bilateral intra-NAc administration of CART peptide. The experiments included both male and female Sprague-Dawley rats, and varying the CART peptide dose and the PS dose. While the average effect of CART peptide was to inhibit PS-induced LMA, the effect of CART peptide on individual PS treated animals was not always inhibitory and sometimes even produced an increase or no change in PS-induced LMA. Upon further analysis, we observed a linear correlation, reported for the first time, between the magnitude of PS-induced LMA and the CART peptide effect. Because CART peptide inhibits PS-induced LMA when it is large, and increases PS-induced LMA when it is small, the peptide can be considered a homeostatic regulator of dopamine (DA)-induced LMA, which supports our earlier homeostatic hypothesis.